1991
DOI: 10.1161/01.cir.84.3.1289
|View full text |Cite
|
Sign up to set email alerts
|

Relation of early hemodynamic changes to final cardiac phenotype and survival after neural crest ablation in chick embryos.

Abstract: Increased stroke volume and cardiac output may be necessary factors for survival in embryos with cardiac dysmorphogenesis and probably are associated with dilation of the ventricular portion of the cardiac tube, which leads to malalignment of the outflow vessel or vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
1
45
1
Order By: Relevance
“…It is possible that these indices of contractility may be operating under different loaded conditions between the control and the experimental groups. This model of neural crest ablation has been shown to result in 100% of embryos with anomalies of the derivatives of the aortic arch arteries (7). Fifty percent of these embryos have interrupted aortic arch, and the other anomalies are less severe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that these indices of contractility may be operating under different loaded conditions between the control and the experimental groups. This model of neural crest ablation has been shown to result in 100% of embryos with anomalies of the derivatives of the aortic arch arteries (7). Fifty percent of these embryos have interrupted aortic arch, and the other anomalies are less severe.…”
Section: Discussionmentioning
confidence: 99%
“…This region corresponds to the cardiac neural crest destined for pharyngeal arches 3 and 4. A recent study by Tomita et al (7) has shown that this particular neural crest lesion results in an 83% incidence of persistent truncus arteriosus and a 17% incidence of double outlet right ventricle, associated with a 100% incidence of aortic arch artery anomalies. After microsurgery, the eggs were sealed with cellophane tape and reincubated in the same high humidity incubator.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Altered blood flow likely affects the aortic arches development. Studies have shown that subsequent to ablation of cranial neural crest, heart morphology and pharyngeal arch vessels (aortic arches) are altered before outflow tract septation normally occurred (Tomita et al, 1991). Alterations in the arch vessel apparatus were present by day three in chick embryos with neural crest ablation at stage 9-10 (Bockman et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tomita el al. (6) demonstrated that ablation of premigratory neural crest destined for the third and fourth pharyngeal arches produced an 83% incidence of persistent truncus arteriosus, and 100% incidence of anomalies of the derivatives of the aortic arch arteries.…”
mentioning
confidence: 99%